Leadership Strategies In Overcoming Educational Problems - Hini Fatimah; Syahrani (CV. ADIBA AISHA AMIRA, 2022)
Education is an important thing in human life. The success of an educational institution is largely determined by the role of leadership. The role of a leader in carrying out and taking various strategies to advance educational institutions is very urgent. Because of its existence in overcoming various problems faced by educational institutions. A leader carries out strategic management as an effort to fortify himself so that educational activities can still be carried out and the quality of education can increase. This research uses a qualitative approach method with library research or literature study. As for the problems discussed, the author uses descriptive analysis method. The results of this study are the leadership of an educational institution must be able to implement strategies to overcome leadership problems in order to be able to create a conducive atmosphere for educational institutions